The Age of Mass Migration in Argentina: Social Mobility, Effects on Growth, and Selection Patterns - Droller, F (Springer International Publishing, 2023)
Argentina was the second largest destination country during the Age of Mass Migration, receiving nearly six million migrants. In this chapter, we first summarize recent findings characterizing migrants’ long-term economic assimilation and their contributions to local economic development. The reviewed evidence shows that Europeans experienced rapid upward mobility in Argentina and immigration contributed positively to the process of economic development. We then turn our focus to the selection patterns of Italian migrants to Argentina—the largest migratory group to this destination. Our analysis of this initial stage of the migrants’ history shows that Italians who moved to Argentina were positively selected on the basis of literacy, complementing existing evidence of rapid upward mobility and contribution to growth at destination. Prepared for the volume “Roots of Underdevelopment: A New Economic (and Political) History of Latin America and the Caribbean” (Felipe Valencia, ed.). We thank Francisco Eslava, Roy Hora, Benjamin Milner, and Felipe Valencia for useful comments and suggestions. © The Author(s), under exclusive license to Springer Nature Switzerland AG 2023.